2017
DOI: 10.18203/2319-2003.ijbcp20175216
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug use practices among dermatology out-patients using WHO core drug use indicators

Abstract: INTRODUCTIONWith the spurge of basic and clinical research activities, and the subsequent recognition of newer dermatological disorders; dermatology, venereology and leprology is now considered to be the one of the most important specialties in a healthcare setup. The skin, the largest organ of the body, epitomize for most of the underlying internal diseases. Dermatological conditions accounts for up to 2% of consultations in general practice worldwide. 1 Dermatological problem in India manifests as primary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…14,15 The current study findings suggested that 63.2% of the drugs were prescribed in the form of tablets, 20.4% were prescribed in the form of creams, 14.7% was in the form of capsules and 1.7% were in the form of syrups, which was similar to the study conducted by Khobragade et al, having 55% in the form of tablets, 23.1% in creams and 6.4% in the form of capsules and Kumar et al, having 35% in the form of tablets, 21% in creams and 4.1% in the form of capsules. 14,15 Under WHO core drug use indicators, in the present study, 100% of the drugs were prescribed by generic names, which was 89.3% in study conducted by Khobragade et al, and just 2.1% in the study by Mukherjee et al 12,14,16 Whereas only 7.9% of the encounters had an antibiotic prescribed in present study, compared to 23.1% in study by Khobragade et al and 34.8% by Mukherjee et al 14,16 Percentage of encounters having at least one steroid prescribed were 12.3% in the present study, was 11.9% in study conducted by Khobragade et al and 51.8% in study conducted by Mukherjee et al 14,16 Percentage of encounters having at least one injectable prescribed were 0% in present study, was 3.1% in study conducted by Khobragade et al and 11.9% in study conducted by Mukherjee et al 14,16 Percentage of prescribed drugs featuring in WHO essential drugs list were 68.9% in present study, was 90.3% in study conducted by Khobragade et al 12,14 Percentage of drugs prescribed by FDCs were 10.8% in current study and 9.75% in study conducted by Mukherjee et al 16…”
Section: Discussionmentioning
confidence: 52%
“…14,15 The current study findings suggested that 63.2% of the drugs were prescribed in the form of tablets, 20.4% were prescribed in the form of creams, 14.7% was in the form of capsules and 1.7% were in the form of syrups, which was similar to the study conducted by Khobragade et al, having 55% in the form of tablets, 23.1% in creams and 6.4% in the form of capsules and Kumar et al, having 35% in the form of tablets, 21% in creams and 4.1% in the form of capsules. 14,15 Under WHO core drug use indicators, in the present study, 100% of the drugs were prescribed by generic names, which was 89.3% in study conducted by Khobragade et al, and just 2.1% in the study by Mukherjee et al 12,14,16 Whereas only 7.9% of the encounters had an antibiotic prescribed in present study, compared to 23.1% in study by Khobragade et al and 34.8% by Mukherjee et al 14,16 Percentage of encounters having at least one steroid prescribed were 12.3% in the present study, was 11.9% in study conducted by Khobragade et al and 51.8% in study conducted by Mukherjee et al 14,16 Percentage of encounters having at least one injectable prescribed were 0% in present study, was 3.1% in study conducted by Khobragade et al and 11.9% in study conducted by Mukherjee et al 14,16 Percentage of prescribed drugs featuring in WHO essential drugs list were 68.9% in present study, was 90.3% in study conducted by Khobragade et al 12,14 Percentage of drugs prescribed by FDCs were 10.8% in current study and 9.75% in study conducted by Mukherjee et al 16…”
Section: Discussionmentioning
confidence: 52%
“…Similar data was found in study of 19 (11.07%) where it was higher than our study 18 (28.61%). Antibiotics were most commonly prescribed class of drugs 22,5 and. 4 The result of the study regarding percent encounter with an antibiotic prescribed (13%) is within the range of WHO.…”
Section: Who Core Prescribing Indicatormentioning
confidence: 99%
“…2 WHO in collaboration with the International Network for the Rational Use of Drug (INRUD) developed core indicators (average number of drugs per encounter, percentage of encounters with an antibiotic prescribed, percentage of drugs prescribed from WHO essential drug list, percentage of fixed drug combination from WHO essential drug list. 5,6 Commonly used drugs for treatment of dermatological conditions include antibiotics, antiseptics, corticosteroids, antifungals, antivirals, anti-histaminic, local anesthetics, emollients, keratolytic, anti-parasitic, vitamins and so on. Irrational drug combinations, over use of multivitamins, emollients, unnecessary use of antibacterial in fungal infections and prescribing drug from same class led to the unnecessary skin diseases.…”
Section: Introductionmentioning
confidence: 99%